Integrierte Planung und Konstruktion von Werkzeugen für die Biegebearbeitung - Franke, Volker (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1998)
The aim of the thesis was to reduce the user interactions needed for planning of bending sequences and to automise the process by taking into account standard and special bending tools. The work focused on the assignment of tools and the determination of toolsets, whereby design, production and administration of tools were considered as well. On the base of a knowledge based and self learning system for planning of bending sequences powerful concepts were developed in order to find optimal solutions in a short time. The technological assignment of tools for single bending sequences is done by the use of a fuzzy based system. So it was possible to implement expert rules for tool selection very simple. Tool design was automated with the aid of a neural network. The network application is divided into two different layers. In the first layer the tool type is selected by classifying the shape of the workpiece. In the second step the tool parameters are calculated with a network which takes into account the particular tool type. The planning system was completed with a rapid tooling system. The tools are constructed out of laser beam cut sheet metal lamellas. With the tool system it is possible to create new tools for complex bent components very rapidly and at low cost